Decreased MUC1 in endometrium is an independent receptivity marker in recurrent implantation failure during implantation window - Fangrong Wu; Xiaoyan Chen; Yingyu Liu; Bo Liang; Hui Xu; Tin Chiu Li; Chi Chiu Wang (BMC, 2018)
Abstract Background It is postulated that women suffered from recurrent implantation failure (RIF) have different endometrial receptivity compared to those who experienced with idiopathic recurrent miscarriage (RM). In this study, expression of common endometrial markers Leukemia inhibitor factor (LIF), mucin 1 (MUC1) and integrin β3 were studied and compared. Methods Fourteen women with RIF, 25 with RM and 20 fertile controls were recruited for endometrial biopsy during implantation window on day LH +  7. Spatial and temporal expression of MUC1, LIF and Integrin β3 were compared using semi-quantitative immunohistochemistry. Association of MUC1, LIF and integrin β3 expression levels with demographic and clinical characteristics were determined. Results MUC1 expression in both luminal and glandular epithelium in women with RIF were significantly lower than that in women with RM and fertile controls. There were no differences in LIF and Integrin β3 expression in endometrial epithelium among three groups. Decreased MUC1 expression were not significantly associated with age, BMI, gravidity, parity, cycle length, progesterone level and previous miscarriage. Conclusions Deceased expression of MUC1 is an independent marker for endometrial receptivity in RIF women, suggesting MUC1 may contribute to the reproductive failure in RIF women.